Efektivitas Strategi Branding Lewat Penempatan Logo dan Super Grafis pada Video Reels Instagram Ikoma ITS - Raden Mohammad Zaky Ar-Rafi; Restu Ismoyo Aji (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
This research analyzes the branding strategy used by Ikatan Orang Tua Mahasiswa ITS (IKOMA) Institut Teknologi Sepuluh November (ITS) through social media, with a focus on the use of interactive Reels videos as a campus approach. The research results show that the use of interactive Reels videos has made a positive contribution in increasing student interaction and awareness of IKOMA and ITS. This research also identifies key factors that influence the success of a branding strategy through social media, such as content quality, creativity, consistency and interaction with the audience. These findings provide important insights for student organizations and educational institutions in understanding the role of branding strategies through social media as a means of strengthening relationships between students and the College.